2023
DOI: 10.1111/jace.19270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La substitution on energy storage properties of (Bi0.2Na0.2Ca0.2Ba0.2Sr0.2)TiO3 lead‐free high‐entropy ceramics

Abstract: In this study, a novel lead‐free high‐entropy ceramic (HEC) system, (Bi0.2Na0.2Ca0.2Ba0.2Sr0.2)(1–3x/2)LaxTiO3 (0 ≤ x ≤ 0.15) (abbreviated as BNCBST‐xLa), was designed to enhance energy storage performance through La substitution and prepared via a hydrothermal method. Results indicate that La doping at A site in BNCBST induces lattice distortion and further improves dielectric relaxation. Moreover, grain growth is inhibited by the La content, which results in an increase in the insulation resistance and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Figure 8 shows the E b and energy storage performance of this study and those of other recently reported lead-free HECs. [10][11][12][13][14][52][53][54][55] It is obvious that the BNCBST-0.15Nb HEC synthesized in present work exhibits significant E b and W rec compared to the other HECs, verifying that Nb doping is an effective strategy to optimize energy storage performance for perovskite HECs.…”
Section: Nb Content T δS Configmentioning
confidence: 84%
See 2 more Smart Citations
“…Figure 8 shows the E b and energy storage performance of this study and those of other recently reported lead-free HECs. [10][11][12][13][14][52][53][54][55] It is obvious that the BNCBST-0.15Nb HEC synthesized in present work exhibits significant E b and W rec compared to the other HECs, verifying that Nb doping is an effective strategy to optimize energy storage performance for perovskite HECs.…”
Section: Nb Content T δS Configmentioning
confidence: 84%
“…12 In our previous studies, A-site disorder perovskite (Bi 0.2 Na 0.2 Ca 0.2 Ba 0.2 Sr 0.2 )TiO 3 and [(Bi 0.2 Na 0.2 Ca 0.2 Ba 0.2 Sr 0.2 ) 0.955 La 0.03 ]TiO 3 HECs were synthesized through hydrothermal method and exhibited strong dielectric relaxation behavior and good energy storage properties (W rec ∼ 2.43 J/cm 3 , E b ∼ 245 kV/cm). 13,14 These studies successfully took advantages of high entropy effect to obtain relaxor ferroelectrics and enhanced energy storage properties. However, the relatively low E b in these HECs is not ideal and inhibited the improvement of the energy storage properties, so further enhancement is required.…”
Section: 𝐸𝑑𝑃mentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman modes within the range of 200-400 cm −1 are characteristic of Ti-O vibrations [65,66]. The modes between 400 and 700 cm −1 are representative of lattice distortion due to TiO 6 octahedral vibration and can be separated in two peaks in the (Bi 0.2 K 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )TiO 3 powder [67]. For the range beyond 700 cm −1 , the modes can be assigned to the behavior of oxygen vibration/rotation [68].…”
Section: Powder Characterizationmentioning
confidence: 99%